Cushions, Kitchens and Christ : Mapping the Domestic in Late Medieval Religious Writing. - Campion, Louise (Religion & culture in the Middle Ages., 2022)
This book is the first full-length study of the significant patterns of domestic imagery in late medieval religious writing in English and their broader cultural significance.